The Dom, a Marginalized Community in the Syrian Music Scene - Daisam Jalo (Music & Minorities)
This article examines the social and economic situation of the music making Dom groups and the social stigmatization to which they are exposed. It argues that the changing sociocultural, political, and economic conditions in Syria have led in the course of the 20th century to a shift in the focus of the Dom’s musical activities to night club music and have thus made the stigmatization worse than ever. On the other hand, the article lists the most eminent features of the Dom’s music in Syria. Moreover, it highlights some Dom figures who were or still are active in the Syrian music scene.